The effects of perspective taking primes on the social tuning of explicit and implicit views toward gender and race - Skorinko, Jeanine Lee McHugh; DiGiovanni, Craig; Rondina, Katherine; Tavares, Amy; Spinney, Jennifer; Kobeissi, Mariam; Lacera, Luisa Perez; Vega, Daniel; Beatty, Paul; John, Melissa-Sue; Doyle, Aidan (Frontiers in Psychology, 2023)
The current research aims to investigate whether perspective taking influences social tuning, or the alignment of one’s self-views, explicit attitudes, and/or implicit attitudes with those of an interaction partner. In six different experiments, participants believed they would interact with a partner to complete a task. Prior to this ostensible interaction, participants were given a perspective taking mindset prime, or not, and information about their ostensible interaction partners views. Participants then completed attitude measures related to the partner’s perceived views. Experiments 1a, 1b, and 2 examined whether perspective taking with an ostensible interaction partner who endorses gender traditional (or non-traditional) views align their self-views with this partner, including implicit self-views (Experiment 2). Experiments 3–5 investigated whether perspective taking leads to social tuning for egalitarian racial attitudes, including when the partner’s expectations of how others will be and when the participant learns their ostensible IAT score at the beginning of the session. We predicted perspective takers would be more likely to social tune their explicit and implicit attitudes to the attitudes of their interaction partner than non-perspective takers. Across all experiments, perspective takers were more likely to social tune their self-views and explicit attitudes than non-perspective takers. However, social tuning never occurred for implicit attitudes. Thus, future research is needed to understand why perspective taking does not influence the tuning of implicit attitudes, but other motivations, like affiliative and epistemic, do.